'You're better out of the way': the experiences of German and Italian women in South Australia, 1939–45. Issue 2 (3rd April 2019) - Harris, Rachel
Abstract: On 30 September 1945, there were 323 females registered as enemy aliens in South Australia, of which 48 were German and 246 were Italian. Much literature exists on the wartime internment of male enemy aliens in Australia but there is very little on the experiences of the mothers, wives and daughters they left behind. By using this group of South Australian women as a case study, this article explores how women classed as enemy aliens during World War II, either by birth or marriage, or those who were Australian-born or naturalised subjects believed to hold non-British allegiances, negotiated everyday life on the home front. Women's oral histories and archival material from the Commonwealth Investigation Branch reveal that while the discrimination and isolation these women faced was mainly a result of their ethnicity, the inequalities they encountered were also shaped by gender.